2018
DOI: 10.1002/mop.31697
|View full text |Cite
|
Sign up to set email alerts
|

Design of a high‐gain wideband antenna using double‐layer metasurface

Abstract: A wideband antenna is studied in this paper using a multi‐layer metasurface structure and implementing a periodic array for enhancing the gain. The performance of the multilayer antenna is improved by using a sub‐wavelength Fabry‐Perot cavity (FPC). The feeding and main radiation patches of the microstrip antenna are placed separately on two substrates, which are stacked on top of each other without an air‐gap in between. Two other substrates are placed within an optimized distance on top of the microstrip ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Although this improvement is desirable, we have not yet achieved our goal at 2.6 GHz, and the bandwidth is only 64.4 MHz. The impedance bandwidth (BW) is the frequency range where the VSWR ≤ 2 [23,27].…”
Section: Double-sided Metallic Superstrate With Metallic Square Ringsmentioning
confidence: 99%
“…Although this improvement is desirable, we have not yet achieved our goal at 2.6 GHz, and the bandwidth is only 64.4 MHz. The impedance bandwidth (BW) is the frequency range where the VSWR ≤ 2 [23,27].…”
Section: Double-sided Metallic Superstrate With Metallic Square Ringsmentioning
confidence: 99%
“…Recently, metasurfaces (MSs) have attracted growing interests of many researchers due to their planar profile, easy fabrication, and also strong beam control capacity [1][2][3][4][5][6]. For phase gradient metasurfaces (PGMS), proposed by Yu et al [7], a wide range of applications have been found, such as anomalous beam bending [8,9], focusing [7,10], surface-plasmon-polariton coupling [11,12], and polarization manipulation. With the ability of tuning the phase range covering 2π, metasurface can be used to improve performance of antenna.…”
Section: Single-layer Broadband Planar Antenna Using Ultrathin High-ementioning
confidence: 99%
“…Due to the exotic features, an appropriate combination of metasurfaces has been found to enhance the MIMO antenna performances such as isolation, gain, and bandwidth. For example, by placing a metasurface above or below of patch resonator, the antenna performance has been reported to enhance markedly [2,11,12,13,14,15,23]. The mechanism for enhancement of the antenna performance is due to the formation of surface wave resonance that creates surface wave propagation along the metasurface for extra resonance [2].…”
Section: Introductionmentioning
confidence: 99%